Agronomic Approaches to Improve the Water Productivity in Wheat (Triticum aestivum) - Kaur, Jagroop; Buttar, G. S.; Kaur, Jagmohan (International Journal of Bio-resource and Stress Management, 2016)
The present scenario of water shortage for agriculture, forced us to produce more from unit quantity of water to meet the food security of ever burgeon population. The underground water table is declining at an alarming rate and water scarcity for irrigation is of great concern especially in Indo-Gangetic plains. The water use efficiency can be increased by doing various agronomic manipulations. In this paper, the effect of sowing methods, mulching and irrigation scheduling has been discussed which impacted water use efficiency in wheat crop. The review suggested that furrow irrigated raised bed planting system (FIRBS) is proved one of the most effective water saving methods which helps in substantial saving of irrigation water. This method decreases irrigation water use without sacrificing economic yield and hence increases the water productivity. These days application of mulch is gaining importance to enhance water use efficiency along with improving soil health. Mulching is useful in conserving soil moisture by minimizing soil evaporation to a great extent. It also improves the microclimate and crop growth and yield. Another option to manage irrigation water can be proper irrigation scheduling. It results in optimum use of irrigation water. The literature shows that there is a considerable saving of irrigation water by scheduling the irrigation water viz., when to apply, how much, etc. Different scientists use different approaches of irrigation scheduling for judicious use of irrigation water in wheat crop.